Analysis of images, social networks and texts : 6th International Conference, AIST 2017, Moscow, Russia, July 27-29, 2017, Revised selected papers /: 6th International Conference, AIST 2017, Moscow, Russia, July 27-29, 2017, Revised selected papers. (2018) - Unknown
No abstract available